Reconsidering Development in Psychoanalysis. Issue 1 (31st December 2022) - Knight, Rona
ABSTRACT: Psychoanalysis has been using scientifically unsupported developmental theories that were proposed over 100 years ago before we had tools to investigate development. This paper will critically examine the theories of Sigmund Freud, Melanie Klein and Donald Winnicott that were based on their ideas of development. These theories and the developmental phases they describe need to be replaced with descriptions of developmental phases that have been scientifically researched and proven for children, adolescents and emerging adults. In this paper a contemporary description and nomenclature for development is described and proposed. A more modern theory of nonlinear dynamic systems is delineated and suggested to replace the unsupported theories used at the start of psychoanalysis that are still being used today and continue to inform our practice of psychoanalysis. This paper is an introduction to a more up-to-date developmental theory, psychoanalytic theory and practice that hopefully we can all participate in and enlarge upon.